Modification of geopolymer with size controlled TiO2 nanoparticle for enhanced durability and catalytic dye degradation under UV light. (10th May 2020) - Maiti, Moumita; Sarkar, Manas; Maiti, Soumen; Malik, Muhammad Akbar; Xu, Shilang
Abstract: Geopolymer- a silica alumina-based polymer has attracted generous amount of interest since the last decades as a promising alternative binder to ordinary Portland cement (OPC) in the construction sector. Proper utilization of industrial waste (Fly ash) and their functionality enhancement is explored in the present exertion by incorporating titanium oxide (TiO2 ) nanoparticle with different size in it. Along with the development of advanced building composite photocatalytic ability of the synthesized product was also assessed. Rutile phase TiO2 NPs were synthesized hydrothermally and annealed at different temperatures which result in differences in their overall size. Different materials characterization techniques have been carried out for confirmation of phase, functional bond, binding energy, and morphology respectively. Geopolymeric (GT) composites (GT30, GT50, and GT100 ) were prepared at ambient temperature using this size-variant TiO2 NPs in fly ash and alkali activator. Integration of TiO2 nanoparticles (5%) enhances mechanical properties where the optimized composite GT30 shows the maximum compressive (53.59 MPa) and tensile strength (6.8 MPa). Mercury Intrusion porosimetry (MIP) and atomic force microscope (AFM) studies indicate that TiO2 nanoparticles of 30 nm (T30 NPs) reduce porosity and roughness of the structure, thus lead to densified matrix and high durability performances. Additionally, GT30 mortar has low water absorption capacity as T30 NPs decrease the apparent volume of permeable voids in its matrix. Degradation of Methylene Blue (MB), a model contaminant was investigated under ultraviolet (UV) light illumination. T30 NPs (1 mg) and GT30 (5 mg) are found to degrade >95% dye solution within 90 min towing to the high surface area of TiO2 NPs and free radical generation. Such outcomes are well fitted in the Langmuir–Hinshelwood first-order rate model. These results will pave the way to explore industrial waste; fly ash in geopolymer for the excellent durability and wastewater treatment through dye degradation under UV light illumination with the aid of TiO2 NPs. Highlights: Rutile phase TiO2 nanoparticle with different sizes have been synthesized. Geopolymer is realized via TiO2 incorporation with fly ash and alkali activator. TiO2 modified geopolymer resulted superior mechanical strength and durability. TiO2 NPs engineered geopolymer showed excellent dye degradation performance.